PENGARUH MEDIA PROMOSI KESEHATAN JINGLE TERHADAP PENGETAHUAN PENCEGAHAN COVID-19 PADA KELOMPOK MASYARAKAT - Pranata, Fanny Cosla; Winarni, Sri; Rachman, Zainol (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
Coronaviruses are a large family of viruses that cause disease in humans and respiratory infections, ranging from the common cold to serious illnesses such as Middle East Syndrome and Severe Acute Respiratory Syndrome. Due to the fact that there are still many people who do not comply with the Covid 19 prevention health protocol, the author took the initiative to conduct research on "The effect of jingle health promotion media on knowledge of Covid 19 prevention at GRJB in Karang Bendo Village, Jajang Surat Hamlet, Rogojampi District, Banyuwangi Regency. This study aims to determine the influence of jingle health promotion media on knowledge of covid 19 prevention in the GRJB group (Jajang Surat Bersatu Youth Movement) in Karang Bendo Village, Jajang Surat Sub district, Rogojampi District, Banyuwangi Regency. This research is a quantitative study using the One Group Pretest Posttest Design method. This pretest-prottest design group is included in the Pre-Experimental Designs (nondesign) research, with a total sample of 30 respondents. The inclusion criteria of respondents are 16 until 28 years old and are members of the GRJB group (Jajang Surat Bersatu Youth Movement). Data collection uses questionnaire directly and the form of intervention or treatment by listening to the jingle to the respondent. The results of the research on the level of knowledge found that there was a change in knowledge from the previous results of the pretest only 96.7 Percent of respondents whose knowledge was categorized as good, after the intervention was 100 percent, it could be concluded that there was a change in knowledge of the respondents after the intervention or treatment. The results of the hypothesis test showed that there was an influence of media jingles about the importance of complying with health protocols in an effort to prevent covid 19 on the knowledge of the GRJB group (H1 was accepted).